Irrigation with wastewater on a Canavalia ensiformis cultivation in substrate treated with coffee dregs vermicompost - Malafaia, Guilherme; Rodrigues, Ronaldo Ferreira; Araújo, Fernando Godinho; Fernandes, Eliana Paula; Leandro, Wilson Mozena; Rodrigues, Aline Sueli de Lima (Científica, 2015)
Taking into account the necessity of creating alternatives to minimize the environmental impacts caused by solid and liquid residues, this study aimed at examining the feasibility of Canavalia ensiformis (jack bean) cultivation in substrates treated with coffee dregs vermicompost and fertirrigated with wastewater. Initially, the vermicompost was prepared using Eisenia foetida worms and different percentages of coffee dregs. To study the C. ensiformis development, experimental units were established, organized in a completely randomized design, with four treatments and eight repetitions. The following parameters were obtained: average number of leaves per plant; height of the aerial part; fresh and dry phytomass of aerial parts and roots, and length of roots. Chemical analyses of irrigation water and cultivation soil were carried out. The results showed that the substrates treated with a compost made of 25% coffee dregs and 75% cattle manure provided the most favorable conditions for E. foetida to grow, and it is suggested as an alternative to vermicomposting. The groups cultivated with the application of coffee dregs vermicompost and irrigated with wastewater presented the best results in terms of the variables chosen to assess plant development. This has possibly resulted from the higher concentrations of N, P and K present in the wastewater and in the substrate treated with the coffee dregs vermicompost. This study points to the potential use of irrigation with wastewater, combined with a substrate treated with coffee dregs vermicompost, in C. ensiformis cultivation.